2003
DOI: 10.2337/diabetes.52.6.1562
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Insulin-Degrading Enzyme Gene Are Associated With Type 2 Diabetes in Men From the NHLBI Framingham Heart Study

Abstract: Linkage studies have mapped a susceptibility gene for type 2 diabetes to the long arm of chromosome 10, where we have previously identified a quantitative trait locus that affects fasting blood glucose within the Framingham Heart Study cohort. One candidate gene in this region is the insulin-degrading enzyme (IDE), which, in the GK rat model, has been associated with nonobese type 2 diabetes. Single nucleotide polymorphisms (SNPs) were used to map a haplotype block in the 3 end of IDE, which revealed associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 26 publications
4
76
2
1
Order By: Relevance
“…30 Here, we found a novel association of rs11187007 with type 2 diabetes and triglycerides, in line with the findings that variants and haplotypes in IDE were associated with FPG, HbA1c and type 2 diabetes. 22,23,30,31 On the other hand, the association study and meta-analysis further confirmed the effect of HHEX rs1111875 on type 2 diabetes in Chinese population, consistent with previous genome-wide association studies and replication studies in other ethnic populations. [15][16][17][18][19]25,26,[32][33][34] The HHEX gene encodes a transcription factor that is also involved in the Wnt signaling pathway and that has been shown to be essential for pancreas development.…”
Section: Discussionsupporting
confidence: 73%
“…30 Here, we found a novel association of rs11187007 with type 2 diabetes and triglycerides, in line with the findings that variants and haplotypes in IDE were associated with FPG, HbA1c and type 2 diabetes. 22,23,30,31 On the other hand, the association study and meta-analysis further confirmed the effect of HHEX rs1111875 on type 2 diabetes in Chinese population, consistent with previous genome-wide association studies and replication studies in other ethnic populations. [15][16][17][18][19]25,26,[32][33][34] The HHEX gene encodes a transcription factor that is also involved in the Wnt signaling pathway and that has been shown to be essential for pancreas development.…”
Section: Discussionsupporting
confidence: 73%
“…Evidence for a putative influence of IDE on the pathogenesis of type 2 diabetes was confirmed in association studies in several independent human populations [15][16][17] and in a recently published meta-analysis [18].…”
Section: Introductionmentioning
confidence: 81%
“…Nevertheless, the preexisting strong biological candidature of IDE is certainly reason enough to prioritize it for further studies. Another reason to target IDE for detailed analysis is the recent demonstration that polymorphisms in this gene also contribute to the risk of type 2 diabetes, which itself appears to be a risk factor for AD [Karamohamed et al, 2003]. Given all available evidence, we consider it highly likely that genetic variation within or extremely close to IDE impacts both disease risk and traits related to the severity of AD.…”
Section: Discussionmentioning
confidence: 99%